(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Basic Life Support (BLS) guidelines provide a structured sequence of interventions that can help revive individuals with life-threatening conditions. Healthcare workers’ knowledge and skills in performing BLS can mean the difference between life and death. This study aimed to evaluate healthcare professionals’ pre-existing knowledge and skills regarding BLS and the effectiveness of BLS training in improving the knowledge and skills of healthcare workers. Method: This observational study was conducted at a tertiary-level hospital in Nepal. A group of 125 participants who were trained during the BLS training course were included in our study. Data were collected through structured pre-test and post-test questionnaires supplemented by direct observation during practical skills sessions. The knowledge and skills of the participants before and after training were compared to evaluate the effectiveness of BLS training in improving the knowledge and skills of healthcare workers. Result: The mean knowledge score of the participants was 62.88% before BLS training and 84.96% after training. The mean skills score was 59.02% before the training and 84.43% after the training. The improvement in knowledge and skills after the training was statistically significant. Conclusion: Participants receiving BLS training show a significant improvement in both their knowledge regarding BLS and their skills in administering BLS.